Globalisation and interdependence in the international political economy : rhetoric and reality - Jones, R. J. Barry (Bloomsbury academic collections. Economics., 2013)
"Globalisation and Interdependence in the International Political Economy addresses central developments within the contemporary international system. The notions of interdependence and globalisation that have accompanied the political discourse of 'a new world disorder' are replete with definitional ambiguities, theoretical difficulties and empirical complexities. Barry Jones offers a critical review and analysis of these concepts, their significance and place within the wider debates of international political economy. He argues that contemporary conditions are complex, with regionalising tendencies cross-cutting those of increasing globalisation, and 'national' impulses surviving even in the face of powerful 'internationalising' forces. Future developments, it is concluded, may also be far more uncertain and turbulent than is widely anticipated. Written by a leading authority, this volume is an effective and compelling introduction to the complex study of international political economy."--Bloomsbury Publishing